Recognition of 1, 3‐Butadiene by a Porous Coordination Polymer. (28th September 2016) - Kishida, Keisuke; Okumura, Yoshikuni; Watanabe, Yoshihiro; Mukoyoshi, Megumi; Bracco, Silvia; Comotti, Angiolina; Sozzani, Piero; Horike, Satoshi; Kitagawa, Susumu
Abstract: The separation of 1, 3‐butadiene from C4 hydrocarbon mixtures is imperative for the production of synthetic rubbers, and there is a need for a more economical separation method, such as a pressure swing adsorption process. With regard to adsorbents that enable C4 gas separation, [Zn(NO2 ip)(dpe)] n (SD‐65; NO2 ip=5‐nitroisophthalate, dpe=1, 2‐di(4‐pyridyl)ethylene) is a promising porous material because of its structural flexibility and restricted voids, which provide unique guest‐responsive accommodation. The 1, 3‐butadiene‐selective sorption profile of SD‐65 was elucidated by adsorption isotherms, in situ PXRD, and SSNMR studies and was further investigated by multigas separation and adsorption–desorption‐cycle experiments for its application to separation technology.